Analisis Kebutuhan Kapasitas Produksi Mortar Instan Menggunakan Metode Perencanaan Kapasitas Rough Cut (Studi Kasus: PT. Bumi Sarana Beton) - setiawan, irwan; Baharuddin, Andi Velahyati; Muhammad, Maula Sidi; Haris, Syukri Agung Wijaya (Jurnal Industri dan Teknologi Samawa, 2025)
The rapid development of the industrial world has increased competition among companies, especially in meeting production needs for large and timely demand. This research aims to understand the production process, predict and analyze capacity requirements, and determine the appropriate instant mortar production target for the companies. Forecasting methods are used to estimated incoming demand, and Rough Cut Capacity Planning (RCCP) is employed to determine the capacity a production facility can provide or need within a certain period. RCCP calculates the required capacity using three inputs: MPS, Production Time, and Historical Proportion. Forecasting results using the Single Exponential Smoothing method with a smoothing factor of 0.9 yield the smallest error indicators for four metrics: MAD, MSE, MFE, and MAPE. RCCP results, with a utility of 0.83 and efficiency of 0.93, indicate that the 2023 production capacity requirement is 239,066,667 minutes, while capacity availability is 184,535,560 minutes, meaning the production target cannot be met on time. To determine the appropriate production target, the company employs two strategies: increasing the production load by adjusting the MPS with a production capability of 276,803 and enhancing capacity by implementing a three-shift system, thereby boosting facility production.